PENGARUH KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA AKUNTAN PUBLIK DENGAN ROLE STRESS SEBAGAI VARIABEL MODERATING - Amilin Amilin; Rosita Dewi (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2008)
The purpose of this research is to analized the influence of organizational commitment to job satisfaction of public accountants with a role stress as moderating variabel. The samples of this research are 54 public accountants that worked at public accountants office which registered in Jakarta. The data were analized by multiple regression method with moderating variabel. The result of this analysis of individual test show that role conflict is not moderated of relation by organizational commitment with job satisfaction. Also with role ambiguity which not moderated of relation by organizational commitment with job satis¬faction. The main practical implication of this research is that the public accountants organization must be attention to jobs expectation of their auditors. Because that is the factors that rising the organizational commitment and in the future it will be to give a high job satisfaction.Keywords: organizational commitment, role stress, role conflict, role ambiguity, job satisfaction.